Site-Specific Labeling of Protein Kinase CK2: Combining Surface Display and Click Chemistry for Drug Discovery Applications - Christian Nienberg; Anika Retterath; Kira-Sophie Becher; Thorsten Saenger; Henning D. Mootz; Joachim Jose (MDPI AG, 2016)
Human CK2 is a heterotetrameric constitutively active serine/threonine protein kinase and is an emerging target in current anti-cancer drug discovery. The kinase is composed of two catalytic CK2α subunits and two regulatory CK2β subunits. In order to establish an assay to identify protein-protein-interaction inhibitors (PPI) of the CK2α/CK2β interface, a bioorthogonal click reaction was used to modify the protein kinase α-subunit with a fluorophore. By expanding the genetic code, the unnatural amino acid para azidophenylalanine (pAzF) could be incorporated into CK2α. Performing the SPAAC click reaction (Strain-Promoted Azide-Alkyne Cycloaddition) by the use of a dibenzylcyclooctyne-fluorophore (DBCO-fluorophore) led to a specifically labeled human protein kinase CK2α. This site-specific labeling does not impair the phosphorylation activity of CK2, which was evaluated by capillary electrophoresis. Furthermore a dissociation constant (KD) of 631 ± 86.2 nM was determined for the substrate αS1-casein towards CK2α. This labeling strategy was also applied to CK2β subunit on Escherichia coli, indicating the site-specific modifications of proteins on the bacterial cell surface when displayed by Autodisplay.